Effects of Coolants of Double Layer Transpiration Cooling System in the Leading Edge of a Hypersonic Vehicle - Luo, Shibin; Miao, Zhichao; Liu, Jian; Song, Jiawen; Xi, Wenxiong; Liu, Chaoyang (Frontiers in Energy Research, 2021)
As a promising and efficient active cooling method, double layer transpiration cooling is introduced into the design of the cooling system in the leading edge of a hypersonic vehicle. The physical model is built combined with hypersonic transpiration cooling, film cooling, heat conduction, porous media heat conduction and convection heat transfer. In addition, effects of different kinds of coolants are considered to reveal cooling mechanisms in different operation conditions. A comprehensive turbulence model validation and mesh independence study are provided. Flow characteristics caused by flow impingement, separation, transition and interaction with the cooling flows are displayed and analyzed in the work. When different kinds of coolants supplied at the same mass flow rate, the coolants with low densities, i.e., H2 and He, have the lowest peak temperature compared with the coolants with large densities, i.e., N2 and CO2. The coolants with low densities have a large ejecting velocity which provides large kinetic energy to penetrate deeply in the porous media. In addition, when the ejecting velocity is large enough, a recirculation is formed in front of the leading edge and pushes the high temperature region located in stagnation region away from the leading edge. However, when the coolants are ejected at the same velocity, the coolants with large densities exhibit better cooling performance.